Characterization and Utilization of Tannin Extract for the Selective Adsorption of Ni (II) Ions from Water - Priya Meethale Kunnambath; Santhi Thirumalaisamy (Journal of Chemistry)
The current paper studies the preparation of a new tannin gel from Acacia nilotica for water purification and waste water remediation. Design of experiments is used for optimizing the tannin gel using tannin extract (Taguchi method) with formaldehyde in the assistance of microwave (TGAN) by the help of iodine number. The feasible combinations were tested in the removal of nickel from simulated and river water. In this study, the effect of adsorbent dosage, pH, and initial metal concentration on Ni (II) biosorption on modified Acacia nilotica tannin gel (TGAN) was investigated. Tannin gel was characterized by SEM, FTIR, XRD, and EDAX. The kinetic data was tested using pseudo-first-order, pseudo-second-order, and intraparticle diffusion model. The results suggested that the pseudo-second-order model (R2 > 0.998) was the best choice among all the kinetic models describing the adsorption behavior of Ni (II) onto TGAN. Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich adsorption models were used to represent the equilibrium data. The best interpretation for the experimental data was given by the Langmuir isotherm and the maximum adsorption capacity 250 mg g−1 of Ni (II) was obtained at pH 5.04 at 296 K. Adsorption of Ni (II) onto TGAN is confirmed qualitatively by the use of atomic absorption spectroscopy. The BOD and COD values are considerably reduced after adsorption.